Penerapan Regresi linier Berganda untuk Menganalisis Jumlah Kecelakaan Lalu Lintas - Gita Aprilia Nurhasanah (Jurnal Riset Informatika dan Teknologi Informasi, 2025)
Traffic accidents are a serious problem that can have negative impacts on both society and the economy of a region. This study aims to analyze the factors contributing to traffic accidents and identify possible prevention measures. The research method involves collecting traffic accident data from various sources, including police reports, witness statements, and medical records. The analysis of accident causes covers aspects such as speeding, non-compliance with traffic regulations, road conditions, and vehicle conditions. The results show that inappropriate speed, the use of mobile phones while driving, and violations of traffic rules are the dominant factors in traffic accidents. In addition, poor road infrastructure conditions and lack of vehicle maintenance also contribute to the high rate of accidents. This study contributes to a deeper understanding of the factors causing traffic accidents and provides insights into prevention strategies that can be adopted by the government and relevant stakeholders. By implementing these measures, it is expected that the number of traffic accidents can be reduced, thereby improving road safety for all road users. Multiple-unit vehicles, such as buses and large trucks, play an important role in mass transportation and logistics. However, traffic accidents involving these vehicles can have serious impacts on road safety and human life. This study aims to analyze the factors contributing to traffic accidents involving multiple-unit vehicles and identify prevention strategies that can be implemented..